2017
DOI: 10.3847/1538-4357/aa7aa5
|View full text |Cite|
|
Sign up to set email alerts
|

Pixel Color–Magnitude Diagram Analysis of the Brightest Cluster Galaxies in Dynamically Young and Old Clusters Abell 1139 and Abell 2589

Abstract: As a case study to understand the coevolution of Brightest Cluster Galaxies (BCGs) and their host clusters, we investigate the BCGs in dynamically young and old clusters, Abell 1139 (A1139) and Abell 2589 (A2589). We analyze the pixel color-magnitude diagrams (pCMDs) using deep g-and r-band images, obtained from the Canada-France-Hawaii Telescope observations. After masking foreground/background objects and smoothing pixels in consideration of the observational seeing size, detailed pCMD features are compared … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 102 publications
0
21
0
Order By: Relevance
“…A candidate for such a simple and efficient methodology to trace the formation history of a galaxy is the pixel color-magnitude diagram (pCMD) analysis (Bothun 1986;Abraham et al 1999;de Grijs et al 2003;Lanyon-Foster et al 2007;Lee et al 2011Lee et al , 2012Lee et al , 2017. This method has not been very widely used until now, but it has potential to be a powerful approach to total understanding of the photometric and structural properties of galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A candidate for such a simple and efficient methodology to trace the formation history of a galaxy is the pixel color-magnitude diagram (pCMD) analysis (Bothun 1986;Abraham et al 1999;de Grijs et al 2003;Lanyon-Foster et al 2007;Lee et al 2011Lee et al , 2012Lee et al , 2017. This method has not been very widely used until now, but it has potential to be a powerful approach to total understanding of the photometric and structural properties of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lanyon-Foster et al (2007) showed that galaxies in variety of morphological types show various and distinct features in their pCMDs, such as prime sequences for early-type galaxies and inverse-L features for spiral galaxies. Compared to the classical photometric and/or structural analysis methods, the pCMD analysis has several advantages: (1) it can be consistently applied to galaxies with any kind of morphology, (2) it considers the photometric and structural properties at the same time, and (3) it is efficient in checking the homology between galaxies in different mass or size scales (Lee et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the stellar population of the galaxy' components, we used newly developed pixelized color-magnitude diagrams. This type of diagram was previously studied in Cook et al (2019); Lee et al (2018Lee et al ( , 2017; Conroy and van Dokkum (2016) and present a new way to understand the stellar populations of galaxies using the magnitudes and colors of each pixel of the models at the different wavelengths. For this work, we have studied the pixelized color-magnitude diagram using the NUV-r colour.…”
Section: Coloursmentioning
confidence: 95%